MEMBUAT ANIMASI PENCEGAHAN 4 TERLALU PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN OKU MENGGUNAKAN ADOBE FLASH CS 6 - Monica, Rara; Faulina , Sri Tita; Trimarsiah , Yunita (JIK : Jurnal Informatika dan Komputer, 2024)
Create a 2D Animation of a Public Service Advertisement About the Importance of 4 Too at the Office of Population Control and Family Planning in Ogan Komering Ulu District Using Adobe Flash CS 6. Animation is an activity to animate, move inanimate objects and is given encouragement, enthusiasm and emotion to become alive and moving. Animation production techniques on computers do not only consist of 2-dimensional and 3-dimensional techniques, but also frame-by-frame motion graphic techniques, which create an illusion of movement of a still image/object frame by frame as if the image were alive. and moves that can be used as an alternative choice in making animation. The method of making motion graphic animated films has the same stages as other animated films, the stages that need to be carried out are drafting story ideas, synopsis, storyline, scenarios, storyboards, collecting sound material, making animation, composition, editing, rendering. An animation has been successfully created with the title "Making Animation The Importance of 4 Too in the OKU Regency Population Control and Family Planning Office Using Adobe Flash CS 6". This animation is made to provide teaching and service to the community, especially in family life, the importance of avoiding too much in order to prevent and save mothers and babies from the impacts that will arise.. Keywords: Animation, Motion Graphic, Frame by Frame, Adobe Flash CS 6